Exciton–Exciton Annihilation in Thermally Activated Delayed Fluorescence Emitter. (2nd June 2020) - Hasan, Monirul; Shukla, Atul; Ahmad, Viqar; Sobus, Jan; Bencheikh, Fatima; McGregor, Sarah K. M.; Mamada, Masashi; Adachi, Chihaya; Lo, Shih‐Chun; Namdas, Ebinazar B.
Abstract: Recent studies have demonstrated that in thermally activated delayed fluorescence (TADF) materials, efficient reverse intersystem crossing occurs from nonradiative triplet exited states to radiative singlet excited states due to a small singlet–triplet energy gap. This reverse intersystem crossing significantly influences exciton annihilation processes and external quantum efficiency roll‐off in TADF based organic light‐emitting diodes (OLEDs). In this work, a comprehensive exciton quenching model is developed for a TADF system to determine singlet–singlet, singlet–triplet, and triplet–triplet annihilation rate constants. A well‐known TADF molecule, 3‐(9, 9‐dimethylacridin‐10(9 H )‐yl)‐9 H ‐xanthen‐9‐one (ACRXTN), is studied under intensity‐dependent optical and electrical pulse excitation. The model shows singlet–singlet annihilation dominates under optically excited decays, whereas singlet–triplet annihilation and triplet–triplet annihilation have strong contribution in electroluminescence decays under electrical pulse excitation. Furthermore, the efficiency roll‐off characteristics of ACRXTN OLEDs at steady state is investigated through simulation. Finally, singlet and triplet diffusion length are calculated from annihilation rate constants. Abstract : A model is developed to extract bimolecular annihilation rate constants for thermally activated delayed fluorescence (TADF) materials using intensity dependent time‐resolved measurements. Using the annihilation rate constants, efficiency roll‐off in TADF organic light‐emitting diodes is explained.